500m gridded surfaces for changes in climate suitability for coffee production in Risaralda, Colombia - Vallejo Arango, Eliana; Navarro Racines, Carlos Eduardo; Ramírez Villegas, Julián Armando; Aguilar-Ariza, Andrés; Delerce, Sylvain Jean (2017)
We used 500m gridded historical and future climate surfaces for Risaralda, Colombia and coffee presences and absences to train species distribution models (suitability). Five methods were used: Generalized Boosting Model (GBM) (Friedman, 2001), Random Forest (RF) (Breiman, 2001), Maxent (Phillips et al., 2006), Generalized Linear Model (GLM) and Generalized Additive Model (GAM) (Guisan et al., 2002).